2015
DOI: 10.3390/cli3020391
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Urban Heat Island Projections for Cities Worldwide: Dynamical Downscaling CMIP5 Global Climate Models

Abstract: Abstract:A new dynamical downscaling methodology to analyze the impact of global climate change on the local climate of cities worldwide is presented. The urban boundary layer climate model UrbClim is coupled to 11 global climate models contained in the Coupled Model Intercomparison Project 5 archive, conducting 20-year simulations for present (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) and future (2081-2100) climate conditions, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 35 publications
(56 reference statements)
0
57
0
Order By: Relevance
“…The UrbClim model has already been successfully validated regarding its energy fluxes, 2 m air temperatures and urbanrural temperature differences for the cities of Antwerp, Ghent (Belgium) and Toulouse (France) in Lauwaet et al (2015) and De Ridder et al (2015). Also the land surface temperatures in the UrbClim land surface scheme, the main focus of the present study, have already been validated in the past with satellite data.…”
Section: Model Evaluationmentioning
confidence: 90%
“…The UrbClim model has already been successfully validated regarding its energy fluxes, 2 m air temperatures and urbanrural temperature differences for the cities of Antwerp, Ghent (Belgium) and Toulouse (France) in Lauwaet et al (2015) and De Ridder et al (2015). Also the land surface temperatures in the UrbClim land surface scheme, the main focus of the present study, have already been validated in the past with satellite data.…”
Section: Model Evaluationmentioning
confidence: 90%
“…Often these sophisticated urban climate models simulate mainly meteorological phenomena based on temperature and/or heat budgets, such as the urban heat island effect (UHI) [11][12][13][14][15][16]. Existing urban modeling studies are able to represent and project the UHI fairly well for different case-study cities worldwide [11,12,15,[17][18][19]. Several studies have indicated that urban areas have an influence on their surroundings and their local-to-regional climate, particularly for temperature, wind, and precipitation [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, bulk schemes allow very fast downscaling of ensemble climate projections (e.g. Lauwaet et al, 2015). Finally, the complexity of the explicit-canyon schemes sometimes makes a consistent incorporation into the host atmospheric model and its maintenance very challenging.…”
Section: Introductionmentioning
confidence: 99%